2020
DOI: 10.3390/su12135371
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Proportion of Plant-Based Foods Available to Shift Social Consumption Norms and Food Choice among Non-Vegetarians

Abstract: Increasing the relative availability of plant-based (versus animal source) foods seems promising in shifting consumption, but it remains unknown how and under what circumstances this happens. We performed two availability manipulations including different foods. The impact on food choice, social norm perceptions about what others do (descriptive) or approve of (injunctive), and salience was assessed. Non-vegetarian participants were visually (Study 1, n = 184) or physically (Study 2, n = 276) exposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 47 publications
(126 reference statements)
0
18
0
Order By: Relevance
“…Raghoebar, S., Van Kleef, E., & De Vet, E. (2020). How physical cues surrounding foods influence snack consumption: The case of covering foods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Raghoebar, S., Van Kleef, E., & De Vet, E. (2020). How physical cues surrounding foods influence snack consumption: The case of covering foods.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it was shown that this single aspect in the food environment (i.e., the relative availability of particular foods) may be perceived differently, and thereby dictate contradictory conduct, in different situations depending on their specific design and implementation (Raghoebar, Van Kleef, & De Vet, 2020b). This may suggest that signals conveyed by or in connection to available foods are relevant to take into consideration when developing such intervention strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that the existence of a higher number of fast food outlets in the residential neighbourhood was associated with a higher endorsement of perceived descriptive norms about common fast food consumption in the neighbourhood, as well as with perceived injunctive norms about appropriate fast food consumption in the neighbourhood. In contrast to the smaller-sized physical cues under study in Chapter 2 (or in small-scale lab experiments such as Raghoebar et al (2020), where participants are situated in the moment of food selection), the neighbourhood-level cues are most probably not directly observable for participants at the moment of measurement. Rather, the survey (including the items about perceived neighbourhood social norms) could be completed anywhere (e.g.…”
Section: Theoretical Reflection On the Main Findings 621 Social Consumption Norms Inferred From Environmental Cuesmentioning
confidence: 99%
“…Indeed, a growing body of experimental studies have provided causal evidence of the normative influence of several of these cues. For instance, in one specific study that focused on the availability of products in a food selection display, Raghoebar, Van Kleef, and De Vet (2020) showed that a greater availability of plant-based (versus animal-source) food products resulted in a higher endorsement of perceived descriptive norms about what other people typically chose, although an effect on food selection was not found.…”
Section: Theoretical Reflection On the Main Findings 621 Social Consumption Norms Inferred From Environmental Cuesmentioning
confidence: 99%